TECHNOLOGIES FOR ELIMINATING SHORTCOMINGS IN ORAL SPEECH IN LESSONS OF VISUAL ACTIVITY - Yuldashev Sadirboy Zhurayevich; Mukhammadzhanov Shahruh Shukhratzhan ogli (Galaxy International Interdisciplinary Research Journal, 2023)
This article discusses one of the crucial problems of our time - the development of technologies for the development of oral speech of children with developmental disabilities in the classroom in fine arts. As an addition to this, the author also provides a list of keywords, summary, used literature in this work.